The role of SIRT1-FXR signaling pathway in valproic acid induced liver injury: a quantitative targeted metabolomic evaluation in epileptic children - Zhao, Mingming; Li, Guofei; Zhao, Limei (Frontiers in Pharmacology, 2024)
Aim: This study aimed to gain deeper insights into the hepatotoxicity mechanisms of valproic acid (VPA), as well as to identify potential risk markers for VPA-induced hepatotoxicity Methods: Twenty-two children with epilepsy treated with VPA monotherapy were divided into a normal liver function (NLF) group, a mild abnormal liver function (ANLF1) group, and a serious abnormal liver function (ANLF2) group based on their liver function indicator levels. The full quantitative targeted metabolomics technique was used to systematically investigate how the differential endogenous metabolic components change with the development of liver injury.Results: A total of 195 metabolic components were quantitatively analyzed. Nineteen identified metabolites, including five organic acids, four short-chain fatty acids, four amino acids, three fatty acids, and three benzenoids, differed significantly among the three groups, showing a strong association with VPA-induced hepatotoxicity. Only three bile acid metabolites, taurodeoxycholic acid, taurochenodeoxycholic acid, and deoxycholic acid, were significantly different between the ANLF1 and ANLF2 groups, increasing at first and then decreasing with the aggravation of liver injury. The mechanistic evaluation showed that SRT1720 activation could alleviate the severity of liver function abnormalities induced by VPA. Immunocoprecipitation indicated that VPA significantly increased the acetylation level of FXR, and the application of agonist SRT1720 can antagonize the acetylation of FXR by VPA Conclusions: Nineteen identified metabolites showed a strong association with hepatotoxicity and three bile acid metabolites changed with the development of liver injury. The SIRT1-FXR pathway was firstly proposed to participate in VPA-induced hepatotoxicity.